Oral Squamous Cell Carcinoma Exosomes Upregulate PIK3/AKT, PTEN, and NOTCH Signaling Pathways in Normal Fibroblasts - Dijana Mitic; Milica Jaksic Karisik; Milos Lazarevic; Jelena Carkic; Emilia Zivkovic; Olivera Mitrovic Ajtic; Jelena Milasin (Current Issues in Molecular Biology)
Exosomes, small extracellular vesicles secreted by various cell types, have gained significant attention in cancer investigations. Isolation and characterization of exosomes derived from DOK (dysplastic oral keratinocyte), SCC (squamous cell carcinoma) and HaCaT (normal skin keratinocyte) cell lines and microRNA profiling were conducted. Magnetic sorting was applied to obtain pure exosomes. Morphology and size were characterized by transmission electron microscopy and nanoparticle tracking analysis. Validation of membrane exosomal markers (CD9, CD63) was performed via Western blotting. MiR-21, miR-31, and miR-133 levels were analyzed in exosomes and parent cells by qPCR. Biological effects of the exosomes were tested by adding them to fibroblast cultures and determining the expression of relevant carcinogenesis markers by qPCR. Exosomes appeared as cup-shaped nano-sized particles, and there was no difference regarding particle diameter and concentration between the three types of exosomes. The oncogenic miR-21 was significantly upregulated both in SCC and SCC-derived exosomes compared to DOK and HaCaT cells and their respective exosomes. However, miR-31 unexpectedly showed the highest expression in normal cells and the lowest in HaCaT exosomes. MiR-133, the tumor suppressor miRNA, was downregulated in both SCC and DOK cells compared to normal (HaCaT) cells, while the opposite situation was observed in exosomes, with HaCaT cells showing the lowest levels of miR-133. The differences in exosome content were reflected in signaling pathway activation in exosome-treated fibroblasts, with SCC exosomes exerting the most potent effect on several cancer-related pathways, notably PIK3/AKT, PTEN, and NOTCH signaling cascades.